Archaeology of dance in Java interpreting the past through iconography - Iyer, Alessandra (SPAFA Journal : a publication of the SEAMEO Regional Centre for Archaelogy and Fine Arts)
Alessa Iyer traces reliefs of the Siva Temple at the Prambanan Complex in Indonesia to reconstruct dance movements of an ancient art form.